Evaluation of Eye Gaze Interaction (International Journal of Engineering and Computer Science, 2013)
Eye gaze interaction added simple and convenient way to communicate with computer. With a growing number of computer devices around us, and the increasing time we spend for interacting with such devices, we are strongly interested in finding new interaction methods which ease the use of computers or increase interaction efficiency. Eye tracking seems to be a promising technology to achieve this goal. In this paper, I present two experiments that evaluate an interaction technique. The results show that algorithm, which makes use of knowledge about how the eyes behave, preserves the natural quickness of the eye. Eye gaze interaction is a reasonable addition to computer interaction and is convenient in situations where it is important to use the hands for other tasks. It is particularly beneficial for the larger screen workspaces and virtual environments of the future, and it will become increasingly practical as eye tracker technology mature